The Influence of Bank Risk and Third-party Funds on Bank Performance in South Korea’s Commercial Bank - Muhammad Faruq Abdulhakim; Vera Intanie Dewi; Feby Astrid Kesaulya; Chris Petra Agung; Adam Hawari (Universitas Mercu Buana, 2026)
Objectives: This study aims to analyze the effects of bank risks (credit, market, and operational risks) and third-party funds (TPF) on the performance of South Korean banks.Methodology: This study employed a quantitative research method to achieve the research objectives. Panel data regression using a fixed-effects model was applied to examine the relationships between the variables. Secondary data were collected from the South Korean Financial Supervisory Service, covering 12 conventional commercial banks. The study period spans from December 2015 to December 2023.Finding: The findings show that market risk, operational risk, and third-party funds significantly influence the profitability of South Korean commercial banks. Meanwhile, credit risk has no significant effect on bank performance.Conclusion: Market risk, third-party funds (TPF), and operational risk are important determinants of bank performance. Effective risk management, consistent with Basel standards, can improve operational efficiency, reduce costs, and increase net profit. However, this study finds that credit risk has no significant effect on bank performance.